Atypical presentation of molar pregnancy at third trimester: a case report from eastern Nepal - Dangal, Binod; Dangal, Rajkumar; Rajbhandari, Swaraj (Journal of General Practice and Emergency Medicine of Nepal, 2021)
A 20 years old primi-gravida lady at 35 weeks of gestation presented to a remote mountainous district hospital with the complaint of per vaginal bleeding on and off with the passage of clots for 10 days. On further examination with an ultrasound scan, she was found to have heterogeneous cystic lesions inside the uterine cavity suggestive of molar pregnancy. She underwent dilatation and evacuation using Bier's forceps after initial resuscitation. Histopathology confirmed the diagnosis of partial molar pregnancy. The postoperative periodwas uneventful and the patient was discharged on the third day with the advice of close monitoring and to follow up with beta-HCG and Chest X-ray.